The Leech's Politeness Principle in the Dialogues of the Short Film 'Ibu' on the Bakar Production YouTube Channel - Miftoqul Khasanah; Budhi Setiawan; Kenfitria Diah Wijayanti (Universitas Sebelas Maret, 2024)
The implementation of politeness principles can still be found in a film, one of which is the short film